STRATEGI BPBD PROVINSI JAWA TIMUR DALAM MENSOSIALISASIKAN PENTINGNYA MITIGASI BENCANA ALAM - Dewi Masrifah (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
ABSTRACT The high level of vulnerability to natural disasters in East Java Province necessitates well-planned pre-disaster mitigation strategies, particularly through the strengthening of disaster education for communities. In this context, the Regional Disaster Management Agency (BPBD) of East Java Province plays a strategic role in designing and implementing disaster mitigation socialization for educational institutions and the general public. This study aims to analyze the disaster mitigation socialization strategies implemented by the BPBD of East Java Province in both formal and non-formal educational settings, as well as to identify the supporting and inhibiting factors influencing their implementation. A descriptive qualitative approach was employed, with data collected through in-depth interviews and documentation of disaster education programs. The data were analyzed thematically to capture strategic patterns and implementation dynamics. The findings indicate that the BPBD of East Java Province implements disaster mitigation socialization through various programs, including the School-Based Disaster Risk Reduction (SPAB) initiative, disaster training and simulation activities, the utilization of disaster education facilities, and the use of print and digital media. These strategies contribute to improving understanding, risk awareness, and preparedness among target groups, although their implementation continues to face challenges such as limited resources, varying levels of disaster literacy, and the wide geographical coverage of service areas. The study concludes that the effectiveness of education-based disaster mitigation socialization is strongly influenced by strengthened cross-sectoral collaboration, the involvement of local actors, and sustained institutional support as key prerequisites for long-term success. ABSTRAK Tingginya tingkat kerawanan bencana alam di Provinsi Jawa Timur menuntut adanya strategi mitigasi prabencana yang terencana, khususnya melalui penguatan edukasi kebencanaan bagi masyarakat. Dalam konteks tersebut, Badan Penanggulangan Bencana Daerah (BPBD) Provinsi Jawa Timur berperan strategis dalam merancang dan melaksanakan sosialisasi mitigasi bencana bagi kelompok pendidikan dan masyarakat umum. Penelitian ini bertujuan menganalisis strategi sosialisasi mitigasi bencana yang diterapkan oleh BPBD Provinsi Jawa Timur pada ranah pendidikan formal dan nonformal, serta mengidentifikasi faktor pendukung dan penghambat implementasinya. Penelitian menggunakan pendekatan kualitatif deskriptif dengan teknik pengumpulan data melalui wawancara mendalam dan dokumentasi terhadap program edukasi kebencanaan yang dilaksanakan. Data dianalisis secara tematik untuk menggambarkan pola strategi dan dinamika pelaksanaannya. Hasil penelitian menunjukkan bahwa BPBD Provinsi Jawa Timur mengimplementasikan sosialisasi mitigasi bencana melalui berbagai program, antara lain Satuan Pendidikan Aman Bencana (SPAB), pelatihan dan simulasi kebencanaan, pemanfaatan sarana edukasi bencana, serta penggunaan media cetak dan digital. Strategi tersebut berkontribusi dalam meningkatkan pemahaman, kesadaran risiko, dan kesiapsiagaan kelompok sasaran, meskipun masih dihadapkan pada keterbatasan sumber daya, variasi tingkat literasi kebencanaan, dan luasnya cakupan wilayah layanan. Penelitian ini menyimpulkan bahwa efektivitas sosialisasi mitigasi bencana berbasis pendidikan sangat dipengaruhi oleh penguatan kolaborasi lintas sektor, keterlibatan aktor lokal, serta dukungan kelembagaan yang berkelanjutan sebagai prasyarat keberhasilan jangka panjang.